Factors Associated with Blood Transfusion Compliance in Children with Thalassemia - Sri Janatri (Indonesian Journal of Global Health Research, 2026)
Thalassemia reduces hemoglobin production, making blood transfusions the primary treatment. Compliance is essential during treatment. To determine the factors associated with compliance with blood transfusion in children with thalassemia.This study used a cross-sectional design involving 57 children with thalassemia at Bhayang Setukpa Lemdikpol Hospital in Sukabumi City, selected using total sampling. Data were collected using a validated structured questionnaire. Data were analyzed using chi-square and logistic regression to determine the relationship between each variable. The results showed a significant relationship between family support (p-value = <0.001), knowledge (p-value = 0.007), and duration of illness (p-value = <0.001) with blood transfusion compliance in children with thalassemia. There was a simultaneous relationship between family support, knowledge, and duration of thalassemia with blood transfusion compliance in children with thalassemia (R Square 0.732).  There is a significant relationship between family support, knowledge, and duration of thalassemia with blood transfusion compliance in children with thalassemia.